1984
DOI: 10.1042/bj2220541
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake associated with Sendai-virus-stimulated chemiluminescence in rat thymocytes contains a significant non-mitochondrial component

Abstract: Sendai virus (150 haemagglutinating units/10(6) cells) stimulates rat thymocytes incubated in medium containing 5 mM-glucose at 37 degrees C to produce luminol-dependent chemiluminescence and a simultaneous increase in O2 consumption of 40%. Stimulation of thymocytes with Sendai virus is accompanied by reduction of exogenous acetylated ferricytochrome c, which is inhibited by superoxide dismutase, and the quantitative conversion of ferricyanide to ferrocyanide, which is not. Replacement of air in the gas space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Thymocytes and peripheral T cells generate ROS through an NADPH oxidase-like system (241,420,480,667,705,959). One study using a mixed culture of primary lymph node cells concluded that NOX2 is not a relevant source of ROS generation by T cells (907).…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Thymocytes and peripheral T cells generate ROS through an NADPH oxidase-like system (241,420,480,667,705,959). One study using a mixed culture of primary lymph node cells concluded that NOX2 is not a relevant source of ROS generation by T cells (907).…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Generation of moderate amounts of ROS (reactive oxygen species) by several non-phagocytic leucocytes, including B-lymphocyte cell lines [1][2][3][4], human tonsillar B-lymphocytes [5], thymocytes [6,7], human NK (natural killer) cells [8,9], human peripheral T-lymphocytes [10] and T-lymphocyte cell lines [11], has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Thymocytes were obtained from male rats of a Wistar strain (100-200 g body wt.) (Kolbuch-Braddon et al, 1984) and suspended in phosphate-buffered saline, pH 7.4 (Cohen et al, 1980), containing 5 mM-glucose. Preliminary experiments showed that Ca2+ detectably but not significantly increased 02 uptake; 0.5 mM-Ca2+ was therefore normally present in the buffered saline (cf.…”
Section: Cells and Cell Fractionsmentioning
confidence: 99%
“…The discovery of an antimycin-and cyanide-insensitive NADPH oxidase in the plasma membrane of various white cell types (Goldstein et al, 1977;Babior et al, 1981;Fantone & Ward, 1982) including rat thymocytes (Kolbuch-Braddon et al, 1984), suggested that the presence of this enzyme system, fortuitously or otherwise, in nuclear preparations might have accounted for the 02 uptake observed earlier. Consistent with this view, the present paper shows that a plasma-membrane-associated NADPH oxidase in rat thymocytes is inhibited by ionizing radiation at levels of exposure which are lethal for small lymphocytes.…”
Section: Introductionmentioning
confidence: 98%